Participative democracy in the Constitutional Cational Assembly and the Constitution of 1988 - Barrientos-Parra, Jorge David [UNESP]; Gasparetto Lunardi, Soraya Regina [UNESP] (Revista Brasileira Estudos Politicos, 2020)
This article discusses the forms and results related to the instruments of participatory democracy in the National Constitutional Assembly and in the 1988 Constitution. For this purpose, the main documents that report this participation are examined. It is a qualitative approach, formalized in two strategies: (i) selective review of the material available in the Brazilian literature and in the Congress database (ii) case study of bills resulting from popular initiative presented since the creation of the Institution in 1988 and 2013 with the verification of how many proposed bills were converted into law and how this process occurs. The main results reveal a very insignificant application of the instruments of right judgment, with a total of 07 bills presented where only 05 were converted into law. As a main conclusion, the instruments of popular initiative to amend the Constitution, the plebiscite and the referendum are participatory instruments almost unknown to Brazilian voters, whose practice would strengthen our young democracy. We point lege ferenda to the need for a constitutional reform that removes the obstacles that currently hinder the exercise of participatory democracy. Legal and Political Science.
Keywords: Constitutional National Assembly; Constitution of 1988; Participative Democracy; Popular Sovereignty